INSTRUCTIONAL DESIGN MODELS: SHIFTING THEORETICAL PARADIGMS - Rama Dwika Herdiawan (Journal of English Language Learning, 2021)
Abstract. Instructional design models have been shifted throughout the years by different scholars because they need to be developed or modified to gain the effectiveness of instructional process. Concerning with the shifts of the related theories, the scholars fomulated a number of patterns in creating the theories in which the aim of this theoretical study is to provide an appropriate understanding in relation to  how to utilize instructional design models. Instruction is regarded as both teaching and learning which have connection with the building of knowledge and skills. Even though there are a lot of instructional design models, a few major distinctions are found in some conditions, e.g. instructional design models present conceptual paradigms in terms of visualizing, performing, and controlling processes for embodying high-standardized teaching and learning artifacts. The exact choice of instructional design models helps us to match the right process with the existing situation. Therefore, instructional design models require a valuable source to match the proper creative process to the proper design situation and also an effective rationale for conducting instructional design research. Keywords: Instrcutional design models, theoretical paradigms